Analisis Pemerolehan Sintaksis Pada Anak Usia Dini (Studi Kualitatif Pada Rizky Ramadhan) - Intan Widia Sari; Mutia Febriyana (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
The purpose of this research is that researchers want to see language acquisition in the field of syntax for a 6-year-old child named Rizky Ramadhan. The source of the data that is the object of this research is the speech or oral utterance of a 6-year-old child named Rizky Ramadhan in the field of syntax. The method used in this research is descriptive research with qualitative data analysis. Data collection techniques carried out by researchers in this study used listening, interviewing and recording techniques. The results of this study indicate that a 6-year-old child named Rizky is able to produce words and sentences in every activity. This can be proven from his daily speech with his interlocutor, namely the researcher, biological mother, and also the child's brother. The theory used in analyzing Rizky's speech refers to Abdul Chaer about sentence classification which includes news sentences (declarative), interrogative sentences (interrogative), imperative sentences, and exclamation sentences (interjective). The results of this study are that Rizky has been able to utter 22 declarative sentences, 15 interrogative sentences, 9 imperative sentences, and 8 interrogative sentences. sentence form as shown in the results.